Overcoming Resistance to Service-Learning’s Use in the Preparation of Teachers for Secondary Agricultural Education: A Reframing of the Method’s Diffusion Challenges - Richie Roberts; M. Craig Edwards (Journal of International Agricultural and Extension Education, 2020)
Although service-learning (SL) has shown promise, its adoption as a method of instruction in secondary agricultural education remains tentative. As such, this philosophical investigation examined how resistance to SL might be uniquely manifested in the context of teacher preparation and the implications for agricultural education if viewed through the lens of Rogers’ (2003) diffusion of innovations theory. After synthesizing related research and theory, we argue the method of instruction’s barriers to adoption include not only a misalignment between teacher educators’ beliefs and practices, but also result from a lack of knowledge, including (a) awareness, (b) how-to, and (c) principles (Rogers, 2003). We also posit that contextual influences at three levels–personal, institutional, and societal –drive or constrain teacher educators’ knowledge of SL during the innovation-decision process. By reframing the problem in this way, implications emerge regarding the difficulties teacher educators may experience as they cross contextual borders and attempt to overcome the knowledge deficiencies likely to influence their pedagogical decision-making. In this regard, we offer an expansion to Rogers’ (2003) innovation-decision process so teacher educators can forecast,isolate, and address better the contextual challenges and knowledge-related problems likely foregrounding their resistance to adopting SL as a method of instruction
Keywords: Diffusion of Innovations theory; innovation-decision process; resistance; service-learning; teacher preparation